FRAUD TRIANGLE SEBAGAI PENDETEKSI KECURANGAN LAPORAN KEUANGAN - Wahyuni, Wahyuni; Budiwitjaksono, Gideon Setyo (Jurnal Akuntansi, 2017)
The financial statements are structured representation of the financial position shows the financial performance of an entity. On the other hand, the Financial Services Authority in Indonesia gave the sanction to capital market players for cheating Financial Statements. This shows that the financial statement fraud cases occurring in Indonesia are part of the failure of an audit conducted by the Public Accounting Firm (KAP). This study aims to examine the influence of fraud triangle in detecting fraudulent financial statements. The object of this study using the financial statements of companies listed on the Indonesia Stock Exchange in the 2012-2014 time period. This study uses 123 data samples are taken using purposive criteria. The data were analyzed using multiple linear regression analysis. The results showed that razionalization significant effect on the financial statements fraud. Meanwhile, the financial stability, external pressure, financial targets, the nature of the industry, ineffective monitoring did not significantly affect the financial statements fraud. This study contributes to the regulators to adopt measures to improve the quality of audits, especially in detecting fraud.